(untitled) (Jurnal Bakti Masyarakat Indonesia, 2019)
Teenagers who violate the rules of criminal law are in the Lembaga Pemasyarakatan (Penitentiary). In a correctional institution for boys in Tangerang, adolescents undergo their prison terms and still get the opportunity to attend school or learn skills. In the interaction of adolescents in correctional institutions, they are often complained about behavior that is not according to rules such as theft, fighting or disturbing friends/ bullying. The inability of adolescents to control their behavior even though they are already in correctional institutions illustrates their difficulties in regulating behavior. Behavioral regulation is part of the human executive function to be able to direct behavior in a purpose so as to make the right decision. Behavioral regulation can be trained with psychological therapy using the game approach. Cognitive Behavioral Play Therapy applied to 10 adolescents in correctional institutions shows that there was a change in the value of behavioral regulation.